Image discrimination reversal learning is impaired by sleep deprivation in rats: Cognitive rigidity or fatigue? - Strobel, Brian K.; Schmidt, Michelle A.; Harvey, Daniel O.; Davis, Christopher J. (Frontiers in Systems Neuroscience, 2022)
Insufficient sleep is pervasive worldwide, and its toll on health and safety is recapitulated in many settings. It is thus important to understand how poor sleep affects the brain and decision making. A robust literature documents the adverse effects of sleep deprivation on cognitive processes including cognitive flexibility, which is the capacity to appraise new feedback and make behavioral adjustments to respond appropriately. Animal models are often used to unravel the molecules, genes and neural circuits that are altered by sleep loss. Herein we take a translational approach to model the effects of sleep deprivation on cognitive rigidity, i.e., impaired cognitive flexibility in rats. There are several approaches to assess cognitive rigidity; in the present study, we employ a pairwise discrimination reversal task. To our knowledge this is the first time this paradigm has been used investigate sleep deprivation. In this touchscreen operant platform, we trained rats to select one of two images to claim a sucrose pellet reward. If the non-rewarded image was selected the rats proceeded to a correction trial where both images were presented in the same position as before. This image presentation continued until the rat selected the correct image. Once rats reached performance criteria, the reward contingencies were reversed. In one group of rats the initial reversal session was preceded by ten hours of sleep deprivation. We compared those rats to controls with undisturbed sleep on the number of sessions to reach performance criteria, number of trials per session, response latencies, correct responses, errors, perseverative errors and perseveration bouts in the initial training and reversal phases. We report that on reversal session one, sleep deprived rats completed a fraction of the trials completed by controls. On subsequent reversal sessions, the sleep deprived rats struggled to adapt to the reversed contingencies despite completing a similar number of trials, suggesting an effect of cognitive rigidity separate from fatigue. We discuss the delayed performance dynamics incurred by sleep loss in the context of fatigue and the implications of using pairwise discrimination reversal as a model to further examine the effects of sleep loss on adaptive decision making.